3D finite element modeling of yarn reinforced mineral matrix: Comparison of damage behavior with experimental data. (1st April 2021) - Homoro, Omayma; Baranger, Thouraya; Michel, Marie
Abstract: Mineral-based composites are presented as a real alternative to the use of Fiber Reinforced Polymer (FRP) composites. However, most studies have focused only on the global mechanical behavior of the mineral-based composites. The objective of this paper is to develop a 3D numerical model in order to predict global and local tensile behavior of glass yarn/ettringitic matrix composites. Two configurations have been studied including dry and pre-impregnated yarn. This modeling is based on a microscopic approach that considers the composite as a heterogeneous material, and that requires defining the properties of the matrix, the yarn and the interface. To simulate the cracked behavior of the matrix and yarn- matrix bond, a discrete model of cohesive zones was adopted. For both dry and pre-impregnated composites, comparisons of numerical and experimental results showed a good agreement in terms of global tensile behavior, cracking and failure mode. This model allowed to analyze the stress and strain states in the yarn, matrix and interface and therefore to deepen the knowledge of the tensile behavior of this type of composite and understand the mechanisms that act during the evolution of the test.